Improving physicians' surgical ward round competence through simulation-based training. Issue 5 (May 2020) - Grünewald, Marc; Klein, Evelyn; Hapfelmeier, Alexander; Wuensch, Alexander; Berberat, Pascal O.; Gartmeier, Martin
Highlights: The intervention group performed better after the training. Students became more confident in conducting ward rounds after the training. The current motivation remained at a constant level throughout the training program. Abstract: Objective: Ward rounds are an essential part of physicians' daily routine. Existing studies suggest that their practical implementation is inconsistent. Therefore, developing interventions to train ward round competence and assessing if they are effective educational tools are crucial goals for research. Methods: We analysed a simulation-based tutorial dedicated to fourth-year medical students, including casework and ward round simulation. We investigated the effectiveness of this intervention regarding ward round competence through a randomized controlled trial. Performance was assessed with the modified/validated surgical ward round assessment tool by two blinded and trained raters. Supplementary, motivation during the ward round tutorial was assessed for all students at different time points. Results: Analysis of the ratings show that, in contrast to the control group (pre: 66.1 vs. post: 64.8 points, p = 0.72), the ward round competence of the intervention group (pre: 62.6 vs. post: 69.6 points, p = 0.0169) improved significantly after participating in the ward round tutorial. Conclusion: The results show that our simulation-based training is an effective way to improve competence of medical students in conducting surgical ward rounds. Practice implications: Participation in ward round trainings is a valuable tool to prepare students for their future professional practise.